ISOLATION OF ESSENSIAL OIL OF NUTMEG (Myristica fragrans Houtt) and ANTIOXIDANT ACTIVITY TEST WITH DPPH - Binawati Ginting; Ratna Maira; Mustanir .; Hira Helwati; Lydia Septa Desiyana; Rohmat Mujahid (Universitas Syiah Kuala, 2018)
The essential oil of the nutmeg plant (Myristica fragrans Houtt) has been obtained from roots, bark, fruit, mace and seeds using Stahl steam distillation. Each essential oil have tested for antioxidant activity with DPPH. Antioxidant activity of essential oil from each nutmeg plant to DPPH with concentration 25, 50 and 100 ppm. Each essential oil did not show strong antioxidant activity but the result of nutmeg isolation had strong antioxidant activity with IC50 that was 80,555 ppm. Based on GC-MS analysis of essential oil of nutmeg isolate obtained myristicin compound with 96.52% area and time Retention 22.127. Myristicin is one of the main components of essential oils of nutmeg plants that play an important role as antioxidants. Keywords: Nutmeg plant (Myristica fragrans Houtt), Essential Oil, DPPH, Antioxidant radicalsREFERENCES Suryanti, Siti. 2014. Metabolit Sekunder Pada Tanaman dan Fungsinya. http://seputarduniasains.blogspot.com Diakses tanggal 2 juni 2015. Gupta, A. D., Bansal, V. K., Babu, V., Maithil, N. 2013. Chemistry, antioxidant and antimicrobial potential of nutmeg (Myristica fregrans Houtt) Journal of Genetic Engineering and Biotechnologyh 11:25-31. Rodianawati, I., Hastuti, P., Cahyanto, M. N. 2015. Nutmeg’s (Myristica fragrans Houtt) Oleoresin: Effect of Heating to Chemical Compositions and Antifungal Properties Procedia Food Science 3:244-254. Masyithah, Z. 2006. Pengaruh Volume dan Konsentrasi Pelarut pada Isolasi Trimiristin dari Limbah Buah Pala Jurnal Teknologi Proses 5(1) Januari; 64-67. Wibowo, S dan Komarayati, S. 2015. Sifat Fisiko Kimia Minyak Cupresus (Cupressus benthamii) Asal Aek Nauli, Parapat Sumatera Utara Jurnal Penelitian Hasil Hutan 33 (2) Juni 2015: 93-103. Nurdjannah, N. 2007. Teknologi Pengolahan Pala. Badan Penelitian dan Pengembangan Pertanian. Bogor. Hellen, M, Vargheese, T.N, Kumari, J, Abiramy, Sajina, Sree, J, 2012, Phytochemical Analysis and Anticancer Activity of Essential Oil From Myristica fragrans, International Journal of Current Pharmaceutical Review and Research. Chatterjee, S, Zareena Niaz, S. Gautam, Soumyakanti Adhikari, Prasad S. Variyar, Arun Sharma, 2007, Antioxidant Activity of Some Phenolic Constituents from Green Pepper (Piper nigrum L.) and Fresh Nutmeg Mace (Myristica fragrans) J. Food Chemistry 101, 515–523. Sulaiman, S. F and Kheng, L. O. 2012. Antioxidant and anti food-borne bacterial activities of extracts from leaf and different fruit parts of Myristica fragrans Houtt. Food Control 25:533-536.Akinboro, A, Kamaruzzaman, M. B, Asmawi, M. Z, Sulaiman, S. F, Sofiman, O. H. 2011. Antioxidans in Aqueous extract of Mirystica fragrans (Houtt) Suppress Mitosis and Cyclophosphamide-induce chromosomal aberrations in Allium cepa L. Cells, Journal of Zhejiang University-SCIENCE B (Biomedicine Biotechnology). ISSN 1673-1581 (Print); ISSN 1862-1783 (Online).www.zju.edu.cn/jzus; www.springerlink.comGinting, B., 2013, Aktifitas Antifungi Ektrak Daun Pala (Mirystica fragrans Houtt), Prosiding Seminar Nasional Kimia tahun 2013. Ginting, B, T. Barus, P, Simanjuntak, L. marpaung., 2013, Isolasi dan Sifat Antioksidan Total Flavonoid Daun Pala (Mirystica fragrans Houtt), Prosiding Seminar Nasional Kimia, Samarinda Ginting, B, T. Barus, P, Simanjuntak, L. marpaung.,2013, Isolasi dan Dan Penentuan Aktivitas Antioksidan Total Alkaloid Daun Pala (Mirystica fragrans Houtt), Prosiding Seminar Nasional Yusuf Banseh Ginting, B, T. Barus, P, Simanjuntak, L. marpaung., 2016, Isolation and Identification of Flavonoid Compound from Nutmeg Leaves (Mirystica fragrans Houtt), Asian Journal Of Chemistry. Ginting, B., Mustanir., Helwati, H., Desiyana, L. S., Eralisa, Mujahid, R. 2017. Antioxidant Activity Of N-Hexane Extract Of Nutmeg Plants From South Aceh Province. Jurnal Natural 17(1) Ramaswany, V. N., Varghese, A., Simon. 2011. An Investigation on Cytotoxic Ternatea L International Journal of Drug Discovery 3: 74-77. ISSN : 0975-4423. Guenther, E. 1987. Minyak Atsiri Jilid 1, terjemahan dari: Essensial oil. Penerjemah: Ketaren S, Universitas Indonesia Press, Jakarta.Harborne, J.B. 1987. Metode Fitokimia: Penentuan Cara Moderen Menganalisa Tumbuhan. Terjemahan dari Phytochemical Methods oleh Kosasih Padmawinata. ITB. Bandung.Sipahelut, S. G. 2012. Karakteristik Minyak Daging Buah Pala (Myristica fragrans Houtt) Melalui Beberapa Cara Pengeringan Dan Distilasi Journal Agroforestri 7(1) Maret 2012.Andini, V., Gupta, S., Chatterejee, S., Variyar, P.S and Sharma, A. 2015. Activity Guided Characterization of Antioxidant Components from Essential Oil of Nutmeg (Myristica fragrans). Vol 52; 221-230.Nagja, T., Vimal, K, Sanjeev, A. 2015. Myristica fragrans: A Comprehensive Review International Journal of Pharmacy and Pharmaceutical Sciences 8 (2).Isnindar., Wahyuono, S., Setyowati, E.P. 2011. Isolasi dan Identifikasi Senyawa Antioksidan Daun Kesemek (Diospyros kaki Thunb.) dengan Metode DPPH (2,2-difenil-1-pikrilhidrazil). Majalah Obat Tradisional. 16(3), 157-164.Ramy, M., Fayed, S.A and Mahmoud, G.I. 2010. Chemical Compositions, Antiviral and Activities of Seven Essential Oils. Journal of Applied Sciences Research. 6(1); 50-62.Indriaty, F., Assah, Y., Mamahani, S.N. 2015. Serbuk minuman berbasis daging buah pala. Baristand. Manado.Morita, T., Jinni, K., Kawagishi, H., Arimoto, Y., Suganuma, H., Inakuma, T, and Sigiyama, K. 2003. Hepatoprotective Effect or Myristicin from Nutmeg (Myristica fragrans) on Lipopolisaccaride/d-galactosamine-induced Liver Injury. J. Agric. Food Chem. 15(6):1.560-1.565.Syarifuddin, I., Kaimudin, M., Torry, R.F., dan Biantoro, R. 2014. Isolasi Trimiristin Minyak Pala Banda Serta Pemanfaatannya Sebagai Bahan Aktif Sabun Jurnal Riset Industri 8(1); 23-31.